Effect of Proton Irradiation on the Defect Evolution of Zr/Nb Nanoscale Multilayers; Metals; Vol. 10, iss. 4 - Laptev R. S. Roman Sergeevich; Lomygin A. D. Anton Dmitrievich; Krotkevich D. Dmitry; Syrtanov M. S. Maksim Sergeevich; Kashkarov E. B. Egor Borisovich; Bordulev Yu. S. Yuri Sergeevich; Siemek K. Krzysztof; Kobets A. G. Andrey Gennadjevich (2020, 2020)
Title screen